2020
DOI: 10.1016/j.cjco.2020.06.005
|View full text |Cite
|
Sign up to set email alerts
|

Improved Exercise Tolerance, Oxygen Delivery, and Oxygen Utilization After Transcatheter Aortic Valve Implantation for Severe Aortic Stenosis

Abstract: Background Transcatheter aortic valve implantation (TAVI) represents an effective therapeutic procedure, particularly in patients with severe aortic stenosis. We hypothesized that the decreased afterload induced by TAVI would improve exercise capacity by enhancing oxygen uptake in working muscles. Methods A standardized exercise test was performed in patients with severe aortic stenosis the day before TAVI and within 5 days thereafter. The main study endpoint was the wo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 41 publications
0
2
0
Order By: Relevance
“…Exercise prevents damage to the heart caused by various types of injury (Pazzianotto‐Forti et al, 2020; Saco‐Ledo et al, 2020; Sjölin et al, 2020; Suppan et al, 2020). As rats with persistent pressure overload are intolerant to physical effort, we used a moderate‐volume, low‐intensity training protocol (de Souza et al, 2020; Mota et al, 2020).…”
Section: Discussionmentioning
confidence: 99%
“…Exercise prevents damage to the heart caused by various types of injury (Pazzianotto‐Forti et al, 2020; Saco‐Ledo et al, 2020; Sjölin et al, 2020; Suppan et al, 2020). As rats with persistent pressure overload are intolerant to physical effort, we used a moderate‐volume, low‐intensity training protocol (de Souza et al, 2020; Mota et al, 2020).…”
Section: Discussionmentioning
confidence: 99%
“…It should be noted, however, that the magnitude of the rise in rSO 2 observed in this study was much lower than in those patients. Furthermore, although values of baseline rSO 2 were comparable, Suppan et al observed improved rSO 2 and cardiac output following cardiopulmonary exercise testing 5 days after TAVI [ 29 ]. Consequently, the rise in rSO 2 observed in this study might not be a short-term change.…”
Section: Discussionmentioning
confidence: 99%